A case of herpes simplex 2 encephalitis with an unusual radiographic manifestation. (2020) - Liu, Fang-Yu; El Mouhayyar, Christopher; Mamtani, Rishi; Dammann, Fabian; Basein, Tinzar
Abstract: Herpes Simplex Virus (HSV) continues to be an important pathogen inflicting encephalitis in adults and children globally that entails high morbidity and mortality. Prompt diagnosis and treatment are the keys to minimize potential sequelae of the disease. Although HSV encephalitis-1(HSVE-1) is well recognized for its radiographic manifestation of temporal lobe involvement owing to its pathogenesis, radiographic features of HSVE-2 are less uniform. Lumbar puncture with HSV PCR testing is the gold standard for diagnosis. However, when lumbar puncture is not immediately obtainable, consideration of HSVE should be entertained in compatible clinical setting even in the absence of characteristic radiographic finding. We report a case of type 2 HSVE with atypical radiographic manifestation involving bilateral basal ganglia.